Formation of nanotubes on commercially pure titanium at high potentials (=10 V) and their electrochemical response. (22nd March 2019) - Haider, Waseem; Shah, U. H.; Shabib, Ishraq; Deen, K. M.
Abstract: The commercially pure titanium (cpTi–2) was anodized at high potentials (≥10 V) in an organic solution containing fluoride ions. The morphology of the nanotubular structure (NTs) depends on the applied electric field as evaluated from the scanning electron microscope images. The internal diameter of the NTs increased from ∼26 to ∼150 nm with the increase in potential from 10 to 60 V. The growth of Ti6 O NTs along the (110) and (112) crystallographic planes and increase in crystallite size as determined from x-ray diffraction patterns is found to be a function of applied potential during the anodizing process. The electrochemical behavior of these anodized samples was evaluated in 1 wt% NaCl solution through potentiodynamic polarization and electrochemical impedance spectroscopy test methods. The NTs formed at high potentials (50 and 60 V) represented relatively smaller Tafel slopes ( b a and b c ) and larger corrosion ( i corr ) and passive ( i p ) current compared to NTs developed at low potentials. These results were in support with the improved kinetic response of the Ti6 O film, predicted from the simulation of impedance spectra. The p-type semiconductive behavior and an order of magnitude higher charge carrier concentration were also exhibited by NTs formed at potential >40 V as confirmed from Mott Schottky analyses.